A comprehensive review of integrated management strategies for damping-off disease in chili - Delai, Chen; Muhae-Ud-Din, Ghulam; Abid, Rimsha; Tian, Tian; Liu, Ruirui; Xiong, Yan; Ma, Shirong; Ghorbani, Abazar (Frontiers in Microbiology, 2024)
Damping-off disease in Chilli (Capsicum annum L.) cultivation is considered one of the significant problems in the world as it severely affects seeds, seedlings, and young plants regardless of the location of cultivation, closed houses, and open fields. Even though chilli is a fruity vegetable popular among all communities and includes various cuisine globally, it is a challenge for farmers to maintain the supply for the growing demand of chilli due to rigorous damage ranging from 20% to 85% caused by this disease. The shelf life and the quality of mature pods are severely affected. Dampingoff disease is mainly caused by soil-borne fungus which belongs to Pythium spp. In addition, Phytophthora spp., Fusarium spp., and Rhizoctonia spp. are also responsible for the disease symptoms. Due to the adaptability to broad environmental conditions and high resistance against synthetic fungicides, it is challenging to control dampingoff on a commercial scale. An integrated disease management approach has shown a promising solution as a remedial measure. In this review, we broadly discuss the current situation of chili diseases, the nature of the damping-off causal agents, the disease's epidemiology, and different disease control mechanisms. Further, we highlight the importance, efficacy, and various techniques of integrated disease management and elaborate prospects in unexplored areas, such as host-pathogen interaction and sustainable disease control measures. The information in this review will help the chili growers with various aspects of the epidemiology and integrated disease management of damping-off in chilli cultivation.